ANALYSIS OF HOSPITAL MANAGEMENT COMMITMENT TOWARDS THE IMPLEMENTATION OF DISASTER MANAGEMENT AT BHAYANGKARA HOSPITAL BANDA ACEH (Proceedings OPTIMAL, 2024)
Disasters are events and series of events that can threaten and disrupt people's lives and livelihoods. In 2004, the earthquake and tsunami in Aceh destroyed hospitals and other health facilities and in 2020 the Covid 19 outbreak occurred which was a national epidemic. The existence of a strong management commitment is very necessary for hospitals to be able to increase hospital readiness in facing disasters. The aim of this research is to analyze management commitment in implementing disaster preparedness at Bhayangkara Hospital. This research is descriptive research with a qualitative approach that collects data using observation, document review and in-depth semi-structured interviews. There were 5 informants, namely 1 key informant, 1 main informant and 3 additional informants. Where the resulting data is then analyzed using an interactive model. The research results show that there is management commitment regarding the organizational structure of disaster management, infrastructure, procedures, resources, financing and training. However, the performance of disaster management has not been optimal even though the hospital uses the concept of activation and deactivation of the organizational structure. Disaster management facilities and infrastructure require additions. And most employees have received training related to disaster management at Bhayangkara Hospital. All informants have a commitment and analysis of the implementation of disaster management using the Hospital Disaster Plan Guidelines as a measuring tool or disaster indicator.